Crystal Engineering in Oligorylenes: The Quest for Optimized Crystal Packing and Enhanced Charge Transport - Meena, Rahul; Pandey, Priya; Zuffa, Caterina; Brázda, Petr; Samolova, Erika; McIntosh, Nemo; Volpi, Martina; Modesti, Federico; Gatsios, Christos; Turetta, Nicholas; Catalano, Luca; Choi, Wookjin; et al. (Crystal growth & design, 2025)
The crystal structures of organic semiconductors are critical when they are integrated into optoelectronic devices, such as organic field-effect transistors (OFETs). In this study, we introduce a crystal engineering approach that leverages weak, nondirectional dispersion forces and steric effects, working together to govern the molecular packing. We investigated how the substitution at the peri-position affects the crystal structure in a series of oligorylene molecules. Upon elucidation of the crystal structures, we found a distinct difference between symmetrical and unsymmetrical derivatives. The unsymmetrical derivatives are prone to forming a sandwich herringbone (SHB) motif, while symmetrical derivatives exhibit a typical herringbone (HB) motif. In most of the rylene derivatives, substitutions at the peri-position triggered an "end-to-face" orientation within the HB structure, rather than an "edge-to-face" orientation, which occurs more often. Results from the Hirschfeld surface analysis provide evidence that the "end-to-face" orientation promotes C-H-π interactions between terminal methyl groups and the π-core of the molecules. While these C-Hmethyl---π interactions contribute to the overall stability of the packing structure, they remain ineffective in enhancing the charge transport properties. In contrast, a particular derivative, tetramethyl perylene (TMP), exhibits a HB structure with an edge-to-face orientation, promoting both C-H---π and π---π interactions. These interactions are crucial for improving the charge carrier mobility, as evidenced by mobility values. For TMP, we could obtain the mobility value of 0.05 cm2 V-1 s-1 in OFETs, whereas a slightly higher mobility of 0.2 cm2 V-1 s-1 was observed with Field-Induced Time-Resolved Microwave conductivity (FI-TRMC) technique.